Effect and mechanism of a novel Mg-Nd-Gd-Sr alloy on osteogenic differentiation of bone marrow mesenchymal stem cells. (November 2022) - Li, Qiangqiang; Yang, Qinglin; Liu, Xiaorong; Liang, Wenqiang; Zhang, Xiaobo; Wang, Yongping
We investigated the effect and mechanism of a novel Mg-3Nd-1Gd-0.3Sr-0.2Zn-0.4Zr (abbreviated to Mg-Nd-Gd-Sr) alloy on the osteogenic differentiation of bone marrow mesenchymal stem cells extracted from Sprague-Dawley rats. Cultured cells were divided into five groups: a control group cultured in osteogenic induction medium alone without Mg-Nd-Gd-Sr alloy extract, and four experimental groups cultured in the same medium with 25%, 50%, 75%, and 100% Mg-Nd-Gd-Sr alloy extracts, respectively. After 14 days of culture, ALP activity was determined and expressions of osteogenesis-related factors Runx2, OCN, and OPN at the mRNA level and Runx2, OCN, and OPN at the protein level were detected by RT-PCR and western blot, respectively. After 21 days of culture, mineralized nodules were detected by alizarin red staining. The results showed that bone marrow mesenchymal stem cells from Sprague-Dawley rats were successfully isolated in vitro using the whole bone marrow adherence method. Flow cytometry revealed that the cells expressed high levels of CD44 and CD90, but low levels of CD31 and CD45. Alizarin red staining indicated the formation of mineralized nodules in all five groups. Compared with the control group, the number of mineralized nodules was increased significantly in the four experimental groups ( p < 0.05). The ALP activity in each group was significantly higher on day 14 than on day 7, and was significantly higher in the four experimental groups compared with the control group ( p < 0.05). Moreover, the ALP activity was highest when the concentration of Mg-Nd-Gd-Sr alloy extract was 75% ( p < 0.05). RT-PCR results showed that, compared with the control group, the mRNA expression of Runx2, OPN, and OCN was significantly higher in the four experimental groups ( p < 0.05), and the highest mRNA expression of Runx2, OPN, and OCN was observed in the 75% experimental group ( p < 0.05). Western blotting showed that Mg-Nd-Gd-Sr alloy extract significantly increased the protein expression of Runx2, OCN, and OPN compared with the control group ( p < 0.05). Our data indicate that the novel Mg-Nd-Gd-Sr alloy can promotes the osteogenic differentiation of bone marrow mesenchymal stem cells isolated from Sprague-Dawley rats. During this process, there is an increase in the expressions of Runx2, OPN, and OCN mRNAs and Runx2, OCN, and OPN proteins.